Pregnancy outcome in hyperemesis gravidarum and flip effect of laboratory clinical indicators of hyperemesis severity - Tan, P.C.; Jacob, R.; Quek, K.F.; Omar, S.Z. (2007)
Objective: To determine Pregnancy outcome in hyperemesis gravidarum and the effect of metabolic, biochemical, hematological and clinical indicators of disease severity on outcome. Study Design: A retrospective study based on 166 women hospitalized for confirmed hyperemesis gravidarum from January 2004 to January 2005. For each woman, three controls matched for age, parity and ethnicity were obtained from our 2004 birth register. The effects of laboratory indicators of hyperemesis severity were separately analyzed within the hyperemesis gravidarum study group. Outcome measures include stillbirths, Apgar score, mode of delivery, low birthweight, preterm delivery, labor induction, pregnancy induced hypertension and gestational diabetes. Analysis was by t-test, Fisher's exact test and multivariable logistic regression analysis. Results: Women with hyperemesis had similar pregnancy outcome compared to controls. In the analysis of laboratory indicators of hyperemesis severity and pregnancy outcomes, hypokalemia (adjusted odds ratio AOR 2.7: 95% confidence interval CI 1.0-6.8) was associated with emergency operative delivery, high creatinine (odds ratio 4.4: 95% CI 1.3-15) with labor induction and raised gamma glutamyltransferase (AOR 7.5: 95% CI 1.2-46) with the development of gestational diabetes. Conclusions: Hyperemesis gravidarum per se was not associated adverse pregnancy outcome. Hypokalemia, high creatinine and raised gamma glutamyltransferase in women with hyperemesis gravidarum were associated with adverse pregnancy outcome.